Register in Reviewing Indonesian Food in Marina Tasha’s YouTube Vlog: Sociolinguistics Study - Salsabila Shafa Azzahra; Ervina CM Simatupang (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research, titled "Register Reviewing Indonesian Food in Marina Tasha’s YouTube Vlog: A Sociolinguistic Study," aims to identify and classify the registers used in food reviews in Bandung, as well as analyze the variation of language and linguistic forms of these registers. The theories employed in this study are those of Martin Joos (1968) on language variation, and George Yule (2006) on linguistic forms. Additionally, the research utilizes a descriptive methodology. This research focuses on the analysis of registers used in food reviews presented in a popular YouTube vlog hosted by Marina Tasha. The study aims to (1) identify the various registers employed by the vlogger when reviewing Indonesian cuisine, and (2) examine how these registers differ in terms of linguistic forms and language variation. The primary data source for this descriptive qualitative research is the script and transcripts of selected food review segments from Marina Tasha's YouTube channel. The data for this study were collected from food review vlog video published on YouTube. The result is revealed 25 words that exhibited variations in language and linguistic forms within registers. The language variations found in the register words in food reviews are formal (5 words, 20%), consultative (6 words, 24%), casual (13 words, 52%), and intimate registers (1 word, 4%). The most dominat register in Indonesian Food in Marina Tasha Youtube is casual.